The MAPT H1 Haplotype Is a Risk Factor for Alzheimer’s Disease in APOE ε4 Non-carriers - Sánchez-Juan, Pascual; Moreno, Sonia; de Rojas, Itziar; Hernández, Isabel; Valero, Sergi; Alegret, Montse; Montrreal, Laura; García González, Pablo; Lage, Carmen; López-García, Sara; Rodrííguez-Rodríguez, Eloy; Orellana, Adelina; et al. (Frontiers in Aging Neuroscience, 2019)
An ancestral inversion of 900 kb on chromosome 17q21, which includes the microtubule-associated protein tau (MAPT) gene, defines two haplotype clades in Caucasians (H1 and H2). The H1 haplotype has been linked inconsistently with AD. In a previous study, we showed that an SNP tagging this haplotype (rs1800547) was associated with AD risk in a large population from the Dementia Genetics Spanish Consortium (DEGESCO) including 4435 cases and 6147 controls. The association was mainly driven by individuals that were non-carriers of the APOE ε4 allele. Our aim was to replicate our previous findings in an independent sample of 4124 AD cases and 3290 controls from Spain (GR@ACE project) and to analyze the effect of the H1 sub-haplotype structure on the risk of AD. The H1 haplotype was associated with AD risk (OR = 1.12; p = 0.0025). Stratification analysis showed that this association was mainly driven by the APOE ε4 non-carriers (OR = 1.15; p = 0.0022). Pooled analysis of both Spanish datasets (n = 17,996) showed that the highest AD risk related to the MAPT H1/H2 haplotype was in those individuals that were the oldest [third tertile (>77 years)] and did not carry APOE ε4 allele (p = 0.001). We did not find a significant association between H1 sub-haplotypes and AD. H1c was nominally associated but lost statistical significance after adjusting by population sub-structure. Our results are consistent with the hypothesis that genetic variants linked to the MAPT H1/H2 are tracking a genuine risk allele for AD. The fact that this association is stronger in APOE ε4 non-carriers partially explains previous controversial results and might be related to a slower alternative causal pathway less dependent on brain amyloid load.